Variation in DNA repair genes XRCC3, XRCC4, and XRCC5 and susceptibility ot myeloma - Hayden, Patrick John (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2010)
Cytogenetic analysis in myeloma reveals marked chromosomal instability. Both widespread genomic alterations and evidence of aberrant class switch recombination, the physiological process that regulates maturation of the antibody response, implicate the DNA repair pathway in disease pathogenesis. We therefore assessed 27 SNPs in 3 genes (XRCC3, XRCC4 and XRCC5) central to DNA repair in patients with myeloma and controls from the EPILYMPH study and from an Irish hospital registry (n=306 cases, 263 controls). For the haplotype-tagging SNP (htSNP) rs963248 in XRCC4, Allele A was significantly more frequent in cases than in controls (86.4% vs. 80.8%; odds ratio (OR) 1.51; 95% confidence interval (Cl) 1.10-2.08; P=0.0133), as was the AA genotype (74% vs. 65%) (P=0.026). Haplotype analysis was performed using Unphased for rs963248 in combination with additional SNPs in XRCC4. The strongest evidence of association came from the A-T haplotype from rs963248-rs2891980, (P=0.008). For XRCC5, the genotype GG from rsl051685 was detected in 10 cases from different national populations but in only 1 control (P=0.015). This SNP is located in the 3' UTR of XRCC5. Overall, these data provide support for the hypothesis that common variation in the genes encoding DNA repair proteins contributes to susceptibility to myeloma.
Keywords: Haematology, M.D.; Ph.D. Trinity College Dublin